120 Communicating Medication-Related Fall Risk via a Patient Portal: What is Important According to Older Fallers in Europe?. (20th December 2019) - Ploegmakers, Kim; Linn, Annemiek; Medlock, Stephanie; Van der Velde, Nathalie; Van Weert, Julia
Abstract: Background: Falls are the leading cause of injury and functional decline in older adults. Medication is a leading cause of falls, second only to mobility impairments. Older adults with Fall Risk Increasing Drug (FRID) use are not aware of having a risk of falling and most of them don't relate fall risk to their drug use. With this European survey we explored if: 1) older adults want to know their personal fall risk, 2) if they want this to be shown via a patient portal, 3) what other elements a patient portal should contain and 4) what potential barriers and facilitators exist for usage of a patient portal. Methods: We distributed a questionnaire in 10 European countries that was filled in by 58 older fallers (mean age 75, 5 years) who visited a geriatric outpatient clinic. Results: Most participants wanted to know their fall risk (82, 8%). The most important elements for the Portal, besides fall risk, were information on FRIDs and patient's illnesses (62%) and access to the medical record (57%). Paying for the system (63%) and privacy issues (53%) were the most important barriers for using the Portal. A user-friendly Portal (57%), the ability to share information with the doctor (47%) and recommendation by doctors (47%) were the most important facilitators. Conclusion: More knowledge dissemination is needed to make older fallers aware of medications that can cause falls. This can be done via a Patient Portal. For a successful implementation, the barriers and facilitators should be taken into account.